Key Aspects of Smart Grid Design for Distribution System Automation: Architecture and Responsibilities. (2015) - Kumar, Y.V. Pavan; Bhimasingu, Ravikumar
Abstract: In the conventional distribution network, systems designed for the control of individual constituents are autonomous with each other with respect to architectures and controlling. Thus, centralized control and integrated functionality are the major challenges faced by the distribution system operators. To overcome these issues, the term "distribution system automation" came into picture by using information and communications technology (ICT)as a resolution that integrate all the critical constituents of a distribution system. This develops a smart environment at power distribution level, called as "smart microgrid" that can optimize the system economy and improve the system resiliency. The major challenge lies in distribution system automation is the selection of proper architecture and communications. In view of all these aspects, this paper present an overview of distribution system automation as a part of smartgrid initiatives and its important features viz., architecture layout and responsibilities.